Assessment of transport kinetics and chemo-mechanical properties of GF/Epoxy composite under long term exposure to sulphuric acid. (January 2021) - Padarthi, Y.; Mohanta, S.; Gupta, J.; Neogi, S.
Highlights: Inter-relation between the acid diffusion mechanism with the changes in chemo-mechanical properties were investigated. The kinetic parameters and transport behaviour validated using Langmuir diffusion model. Detailed mechanistic investigation into the changes of the network structure of the GF/Epoxy composite exposed to aqueous 10% sulphuric acid solution. Tensile strength reduction of 54% reduction and flexural strength reduction of 61% of GF/Epoxy composites for long exposure of 3010 hours in the aqueous 10% sulphuric acid solution. Effectively useful to design the service life and monitor health of the GF/Epoxy composite immersed in aqueous 10% sulphuric acid solution. Abstract: Glass Fibre-Epoxy (GF/Epoxy) composites are being the choice of material when exposed to inorganic acids such as sulphuric acid due to its superior corrosion resistance properties. Water diffusion into GF/Epoxy composites is well-reported. However, inter-relation between acid diffusion mechanism and its analogous influence on chemo-mechanical properties is never investigated with greater details. In this work, the transport behaviour of aqueous 10% sulphuric acid solution into GF/Epoxy composite and its complex inter-relations with the cross-linking density, morphology and mechanical properties is presented. The transport of aqueous solution of 10% sulphuric acid in the composite was quantified by gravimetric analysis and confirmed by the Energy Dispersive X-Ray Spectroscopy (EDX). The kinetic parameters were evaluated and compared using Fickian and Langmuir diffusion models, where the Langmuir model described the transport behaviour better. Analysis of thermomechanical properties such as storage modulus is characterised by dynamic mechanical thermal analysis (DMTA). The free volume distributions are estimated using positron annihilation lifetime spectroscopy (PALS). The indication of an increase in cross-link density with the acid exposure is further validated by Fourier-transform infrared spectroscopy (FT-IR) analysis. In the absence of substantial chemical degradation and with increased cross-linking density, the deterioration in the mechanical properties is attributed to the erosion of epoxy resin confirmed by the morphology performing Field Emission Scanning Electron Microscope (FE-SEM) analysis. The acid diffusion mechanism results show promising prospects of selecting and designing GF/Epoxy composites for industrial storage and manufacturing facilities containing aggressive environments Graphical abstract: Image, graphical abstract